Town and country planning in the UK - Cullingworth, Barry (Routledge, 2006)
This extensively revised edition reinforces this title's reputation as the bible of British planning. It provides an explanation of the nature of planning, the institutions and organizations involved, the plans and other tools used by planners, the system of controlling development and land use change and planning policies pursued